Pleomorphic Adenoma of Hard Palate: A Case Report - Zahra Pourgholi Takrami; Tayebe Ebrahimi; Forough Abbasian (Journal of Craniomaxillofacial Research, 2024)
Salivary gland tumors are rare and account for only 2-3% of head and neck tumors, most of which are benign. Pleomorphic adenoma is the most common salivary gland tumor. This tumor mostly involves the parotid gland. However, if it occurs in the minor salivary glands, the palate is the most common site, followed by the lips, buccal mucosa, floor of the mouth, tongue, tonsils, pharynx, retromolar trigone, and gingiva. It usually presents as a slow-growing, painless submucosal mass on the hard palate. For a definitive diagnosis, it is necessary to perform a preoperative core biopsy for histopathological examination and Computed Tomography to evaluate the erosion of the hard palate and the severity of the erosion. We aim to describe the clinical, and radiological features, as well as the management of this rare localization of pleomorphic adenoma. In this case, a 30-year-old Iranian male patient with pleomorphic adenoma of the small salivary glands of the hard palate with the chief complaint of painless swelling on the left side of the palate for the past 5 years was reported. Although pleomorphic adenoma is a common entity, it is still a challenging tumor for pathologists, radiologists and surgeons. Various histological and topographic features make this tumor unique. Computed tomography and correct histopathological diagnosis are necessary to establish an appropriate surgical treatment, to achieve complete removal of the lesion through extensive local excision with periosteum or bone removal if involved to prevent recurrence. Keywords: Hard palate; Pleomorphic adenoma; Salivary glands; Rare benign tumor.